Auto-antibodies to type I IFNs can underlie adverse reactions to yellow fever live attenuated vaccine - Bastard, Paul; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Chbihi, Marwa; Le Voyer, Tom; Rosain, Jérémie; Philippot, Quentin; Seeleuthner, Yoann; Gervais, Adrian; Materna, Marie; de Oliveira, Patricia Mouta Nunes; Maia, Maria de Lourdes S.; et al. (The Journal of experimental medicine, 2021)
Yellow fever virus (YFV) live attenuated vaccine can, in rare cases, cause life-threatening disease, typically in patients with no previous history of severe viral illness. Autosomal recessive (AR) complete IFNAR1 deficiency was reported in one 12-yr-old patient. Here, we studied seven other previously healthy patients aged 13 to 80 yr with unexplained life-threatening YFV vaccine–associated disease. One 13-yr-old patient had AR complete IFNAR2 deficiency. Three other patients vaccinated at the ages of 47, 57, and 64 yr had high titers of circulating auto-Abs against at least 14 of the 17 individual type I IFNs. These antibodies were recently shown to underlie at least 10% of cases of life-threatening COVID-19 pneumonia. The auto-Abs were neutralizing in vitro, blocking the protective effect of IFN-α2 against YFV vaccine strains. AR IFNAR1 or IFNAR2 deficiency and neutralizing auto-Abs against type I IFNs thus accounted for more than half the cases of life-threatening YFV vaccine-associated disease studied here. Previously healthy subjects could be tested for both predispositions before anti-YFV vaccination.